Clinical and endoscopic diagnostics of foreign bodies of the respiratory tract in children - Shamsiev Jamshid Azamatovich; Ruziev Jasur Aslidinovich; Dusyarov Jaloliddin Toyirovich (International Journal on Integrated Education, 2021)
For the period from January 2000 to June 2019, 1355 children with suspected foreign bodies of the respiratory tract were inpatient treatment and examination in the department of thoracic surgery of the 2 SamMI clinic. The main group of children consisted of children of the first 7 years of life (88.6%), of which the most numerous was the group of children of early age (56.3%). Of the 1355 children hospitalized with suspected foreign bodies of the respiratory tract, 407 (30.0%) had the diagnosis excluded, and 948 (70.0%) had the diagnosis confirmed. Among the examined patients, 858 boys (63.3%) prevailed, compared with 497 girls (36.7%). Children from rural areas prevailed 4.5 times over urban areas, 1107 (81.7%) versus 248 (18.3). 1162 (85.8%) children were admitted in a moderately serious condition. A serious condition was noted in 167 (12.3%) patients. An extremely serious condition when seeking help was observed in 24 (1.8%) children. In addition, children who aspirated organic foreign bodies into the respiratory tract 759 (80.1%) significantly prevailed, compared with children who aspirated inorganic foreign bodies 172 (18.1%). 17 (1.8%) have self-withdrawal.